MENINGKATKAN HASIL BELAJAR SIKLUS AIR MENGGUNAKAN MODEL INVESTIGATION, INTELLECTUALLY, TOURNAMENT - Radiansyah; Raihanah Sari; Fathul Jannah; Masdiyarti (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Students’ learning activities at schools are less active; they find difficulties understanding the materials. The learning results are low because educators have not used an effective learning model. This study aimed to improve the teaching-learning activities and the students’ learning outcomes by using GI, SAVI, and TGT models. It was conducted at grade V of SDN Madang, Kabupaten Tabalong, South Kalimantan. This research utilized Classroom Action Research (CAR) which was conducted in 4 meetings. Data were obtained through observation sheets and evaluation tests of students’ learning outcomes. The data analysis was calculated based on the percentage scale and indicators of learning completeness. The results showed that the activities of educators scored 40 with very good criteria. It was found that 90% of students were very active, and 100% of students’ learning outcomes were complete. The conclusion was that learning through GI, SAVI, and TGT was effective. The activities of educators were very good, the students’ activities were increasing, and the learning outcomes on the water cycle material were complete